Genetic Alterations in Pendrin (SLC26A4) Gene in Adult Hypothyroid Patients - Mukherjee, Sourav; Guha, Manalee; Adhikary, Bidisha; Bankura, Biswabandhu; Mitra, Pubali; Chowdhury, Subhankar; Das, Madhusudan (Hormone and Metabolic Research, 2017)
Current study was aimed to screen the SLC26A4 gene in 127 nonautoimmune and noncongenital hypothyroid patients, who were under optimal iodine nutrition and devoid of any characteristics of Pendred syndrome from eastern part of Indian population. 8 single nucleotide variants/mutations were identified in heterozygous state in 20% patient population, which include 1 novel nonsynonymous (p.C18S), 1 novel intronic (g.942C>A), 3 known nonsynonymous (p.S23X, p.V239D, and p.I455F), and 3 known intronic (g.23034G>T, g.29641C>G, and g.33893T>C) variants. Only g.23034G>T was noted also in homozygous state in 2% patient population. However, Controls exhibited only the variations g.23034G>T and p.I455F. Therefore, present study reports for the first time that the observed novel variants in pendrin gene might be linked with autoimmune negative hypothyroidism, without any characteristics of Pendred syndrome and/or congenital hypothyroidism. While, all observed known variants/mutations were reported with either Pendred syndrome and/or congenital hypothyroidism earlier, but never with nonautoimmune adult hypothyroidism solely. Thereby, the absence of any features of Pendred syndrome and/or congenital hypothyroidism in patients with observed known nonsynonymous variants/mutations may be due to either heterozygous state of each variant or differential domain specific activity of ions trafficking in the respective organ. The analysis of amino acid change at least for p.C18S, p.S23X, and p.V239D in correlation with phenotypic characteristics of respective patients might assume a possible effect on protein structure and function. Altogether, we report for the first time that genetical variations in SLC26A4 gene could play an important role in development of nonautoimmune adult hypothyroidism.
Keywords: adult hypothyroidism; pendrin; polymorphisms; mutations; India; SLC26A4